Trafficking Sexuality Power Relations to Women and Children in Makassar City - Mutiara, Indah Ainun; Kasnawi, Tahir; Mustadjar, Musdalia; Adam, Arlin; ., Suardi (KnE Social Sciences, 2024)
This study aims to determine the factors that cause the sex trafficking of women and children in Makassar City. This research is a qualitative descriptive study using a bibliography study to obtain comprehensive research results. The research location is located in Makassar City, South Sulawesi. The types of data used include primary data, secondary data, and tertiary data. Data techniques were used in interviews and literature studies. Data analysis uses an interactive analysis model. The findings of this study are that there are power relations that result in women and children becoming victims of vulnerable groups. Perpetrators have higher power so they can oppress victims to carry out trafficking to violence. Sexual violence in personal relationships also includes violence perpetrated by husbands as a representation of the power of sexuality. In addition, there are other factors such as poverty, job seekers, low education levels, broken families, and a history of sexual violence. Keywords: power relations, trafficking, women and children